MEMUTUSKAN MENGATUR WAKTU BELAJAR: SUATU UPAYA PERBAIKAN LINGKUNGAN BELAJAR DENGAN PEMBELAJARAN DISTRIBUTED PRACTICE - Mufidah, Yenny Imroatul (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
At the time of teaching, the teacher has several methods used to support the learning program that has been made. One method used to train techniques is the method of distribution practice. The method of distribution practice is the principle of regulating the turnover of material in learning that is carried out through alternating arrangements of rest periods. Building knowledge has focused on distributed practices to make learning and remembering something new, easier for the brain. This paper aims to describe the steps for deciding to study time to improve the learning environment by learning distributed practice. From the discussion concluded: 1) Subjectively and comparatively there are types of distributed practice learning, namely distributed practice itself and mass practice. to show the two extremes of the break-to-work continuum, involving longer periods of rest and shorter periods of active practice (that is, work), and mass practices that involve less time in rest and longer in active practice (working) . Objectively to define both distribution schedules, especially when distributive effects on skills are continuously different from one training session. In this situation, the practice distributed can be defined as a training session in which the amount of rest time equals or greater than the amount of time in work, while a shared practice is then defined as a practice schedule where there is a greater amount of time in work than rest. 2) in general, most students learn a lot before and during the exam and ultimately are unable to remember most of the texts learned during the exam. 3) The act of learning in school is aimless, while activities that give rise to learning in the real world are goals. When the learning environment has an appropriate design, student attitudes and motivation increase. In addition to the academic success of students, he found that learning makes students happy during the learning process by giving them a rich learning experience, on the other hand psychological transformation is based on prerequisite skills, knowledge, and motives. When these prerequisites have not been developed in students, generic contradictions arise. The act of learning [not an activity] is a prerequisite for obtaining certain material, but they cannot be formed (obtained, learned) without being involved in the appropriate material. It is impossible to learn the appropriate learning actions first and then study the material. The actions, content, structure, and course are determined by the object; there is no formal action without content or aimlessly to be transferred to different materials. 4) Today The way to deliver academic information can only be understood by students when they join several new features of the academic learning environment that characterize the digital age. Without knowing how to take advantage of these new features, scholars and graduates will experience successful difficulties in the global economy characterized by three main features: competition and cost, globalization, and information intimacy.